2020
DOI: 10.3390/ijerph17061950
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis on Intervention Effects of Physical Activities on Children and Adolescents with Autism

Abstract: This paper aimed to discuss the intervention effects of physical activities on children and adolescents with autism with a meta-analysis so as to serve as a reference to further relevant research on the same topic. As for research methods, by searching in CNKI (China National Knowledge Infrastructure), WanFang data, VIP Database for Chinese Technical Periodicals, PubMed, Scopus, Web of Science, and other databases, this study collected randomized controlled trials (RCTs) on the intervention of physical activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 16 publications
(78 reference statements)
4
51
0
5
Order By: Relevance
“…It can be assumed that a high level of PA, including sports, increases assertiveness by enhancing self-esteem. Additionally, studies regarding the effectiveness of structured PA programs to improve communication skills for adolescents with autistic spectrum disorder (ASD) support the findings of this study (Huang et al, 2020 29) , Zhao & Chen, 2018 30) ). Huang et al's (2020) meta-analysis concluded that PA has a significant positive impact on communication skills of adolescents with ASD 29) .…”
Section: ) Association Between Experience Of Physical Activity and Assertiveness Among University Studentssupporting
confidence: 79%
See 1 more Smart Citation
“…It can be assumed that a high level of PA, including sports, increases assertiveness by enhancing self-esteem. Additionally, studies regarding the effectiveness of structured PA programs to improve communication skills for adolescents with autistic spectrum disorder (ASD) support the findings of this study (Huang et al, 2020 29) , Zhao & Chen, 2018 30) ). Huang et al's (2020) meta-analysis concluded that PA has a significant positive impact on communication skills of adolescents with ASD 29) .…”
Section: ) Association Between Experience Of Physical Activity and Assertiveness Among University Studentssupporting
confidence: 79%
“…Additionally, studies regarding the effectiveness of structured PA programs to improve communication skills for adolescents with autistic spectrum disorder (ASD) support the findings of this study (Huang et al, 2020 29) , Zhao & Chen, 2018 30) ). Huang et al's (2020) meta-analysis concluded that PA has a significant positive impact on communication skills of adolescents with ASD 29) . These conventional studies and the evidence from this study, indicate that an increase in PA levels improves assertiveness among university students.…”
Section: ) Association Between Experience Of Physical Activity and Assertiveness Among University Studentssupporting
confidence: 79%
“…31,[40][41][42]47 Previous research suggests that both PA and exergaming interventions could be associated with improvements in MS and EF in children with ASD. 48 Although previous studies have directly compared PA and exergaming interventions, to the best of our knowledge no studies have directly compared the effects of an 8-week traditional PA intervention, an exergaming intervention, and a control condition on MS and EF in children with ASD. Our primary aim was to investigate the effects of two types of interventions, SPARK and exergaming (Kinect), on MS and EF in children with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle modifications may have a significant role in IBD and mental disorders. Patients with IBD should be encouraged to exercise because physical activity may improve psycho-logical well-being, reducing anxiety and depression, as well as having a preventative or mitigated role against Alzheimer's disease [70], Parkinson's disease [71] and ASD [72]. Also, IBD patients should avoid alcohol consumption and narcotics use that have been correlated with comorbid mental illnesses and worsening of IBD course [73].…”
Section: Managementmentioning
confidence: 99%